Carroceiros de Cruz Alta/RS: trabalho de coleta de materiais recicláveis e disputas por reconhecimentos sociais - Cidade, Rodrigo Berttoni (2022)
This dissertation thematizes work relationships of cart drivers and their social strategies to maintain themselves in the collection of recyclable materials, in the municipality of Cruz Alta-RS. The research aims to understand the social processes that produced workers who collect recyclable materials, the daily work in the city and the social struggles to remain in the activity, in the face of the growth of animal rights movements. The research used a qualitative approach. The research sample consisted of twelve cart drivers, residents of different neighborhoods, chosen for their participation in resistance struggles in maintaining their craft and for participating in a social project instituted by the municipal power. The research data were collected from a semi-structured interview and from the observation of a daily work day of a cart driver. The life trajectories of these cart drivers are marked by processes of social exclusion in rural areas, lack of work opportunities in urban areas and the precariousness of education and social assistance policies. Cartwrights seek to establish partnership and care relationships with their horses, to keep them well fed and able to do the job. Cart drivers organize their daily work in different ways, but they always have “luck” to find a large amount of recyclable materials or receive donations of furniture, appliances, money, food, clothes, among other consumer goods. Cart drivers make up the family income through the sale of recyclable waste and through income transfer programs, which are difficult to balance in managing family needs and maintaining the animal and equipment on the cart. The municipal administration does not have permanent laws and public policies for the social recognition of the cart driver's craft. The use of horses has become a social problem, built by animal rights societies and the passing of animal rights protection laws. The cart drivers organize struggles for the rights to work, access to the city and recyclable materials, as well as raising debates on the environmental importance of work, for the reduction of waste discarded by the society of Cruz Alta. It is concluded that the lack of legal recognition of the work and the performance of socially organized agents in defense of animals are challenges for the continuity of the work of the cart drivers.